Toxicity bioassay on the effects of four poisonous plants on Tilapia nilotica - Campo, Exelita M.
A toxicity bioassay on the effects of the plant extracts of Croton tiglium, Ricinus communis, Thevetia Peruviana and Anamirta cocculus on the test animal, Tilapia nilotica fry was conducted to determine the feasibility of utilizing the aforementioned plants as a source of molluscicide with respect to the safety of T. nilotica.